EXTRACTION-PHOTOMETRIC DETERMINATION OF NORSULFAZOLE BY MEANS OF METHYLENE BLUE BASIC DYE (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Interaction of norsulfazole (sulfathiazole) sodium salt with methylene blue basic dye has been studied. Optimal conditions for formation of ionic associate have been determined. It has been estimated that the ionic associate forming may be extracted by means of single extraction procedure at equal volumes of aqueous and organic phases within 8.5–10.0 pH range. Submitting to the Beer’s law observed within 3.8–40.0 mcg/mL norsulfazole contents, light adsorption molar coefficient value at 650 nm wavelength is 20900·300 (L·mol-1·cm-1). Norsulfazole sodium salt interacts with methylene blue in 1:1 molar ratio. The elaborated technique has been applied for determination of norsulfazole in drug tablets.
Keywords: norsulfazole (sulfathiazole) sodium salt; methylene blue; formation of ionic associate; elaborated technique